BS EN 60287-1-2. Electric cables. Calculation of the current rating. Part 1. Current rating equations (100 % load factor) and calculations of losses. Section 2. Sheath eddy current loss factors for two circuits in flat formation (11th February 2021) - British Standards Institution,
No abstract available